Still life paintings - Bradley, Leah Martine, author (Colorado State University. Libraries, 1991)
My paintings speak of order, energy, and at times, of magic. These are phenomena that I sense in nature and in the patterns and rhythms of daily life. I choose to paint simple household objects for their multiple personal associations and for their associations with women's lives and women's work. When I remove a few of these objects from the general clutter and honor them with their own space and light, I celebrate the innate value and beauty of the objects, as well as their use in everyday life. The quiet simplicity of the objects, and their stable, careful arrangement also make connections for me between the order of daily life and the grander order of nature. When I surround paintings with fabricated borders, the images feel charged by the livelier energy of the borders. Like icons, the objects within are enclosed and enshrined, and the pieces as a whole have a charm-like or magical quality. Thus my paintings also refer to the sacredness of the repeated patterns of daily chores and to the sense of order that make our lives possible and give them meaning.